The role of error risk taking and perceived organizational innovation climate in the relationship between perceived psychological safety and innovative work behavior: A moderated mediation model - Elsayed, Ahmed M.; Zhao, Bin; Goda, Abd El-mohsen; Elsetouhi, Ahmed M. (Frontiers in Psychology, 2023)
To better understand how to motivate innovative work behavior (IWB) at the individual level in organizations, we investigate the link between perceived psychological safety and IWB and the role of error risk taking and perceived organizational innovation climate in this study. In particular, we hypothesize a moderated mediation model in which (a) perceived psychological safety is positively related to IWB, (b) error risk taking mediates the positive relationship between perceived psychological safety and IWB, and (c) perceived organizational innovation climate strengthens the positive link between error risk taking and IWB and the mediated link between perceived psychological safety and IWB via error risk taking. We tested the hypothesized model using data collected from 315 full-time employees working at six information and communication technology companies in a high-technology business district of Egypt. The findings largely support our hypotheses. We conclude by discussing the theoretical and practical implications.